Navigating Crisis: An Intersectional Analysis of Marginalized Women’s Role in Sustaining Community Cooperatives Through The Covid-19 Pandemic - Widyaningtyas, Rizky Septiana (The Indonesian Journal of Socio-Legal Studies, 2025)
This study analyzes the challenges faced by PEKKA women in Bantul regarding economic empowerment amid the Indonesian government's social restriction policies. It also explores the strategies these women have implemented to survive and strengthen community cooperatives during and after the pandemic. Using a socio-legal method with an intersectional approach, the results indicate that the pandemic and social distancing measures have significantly impacted the economies of female-headed households compared to those supported by both husbands and wives. This impact is particularly pronounced for women who run small businesses that had to close during the pandemic. PEKKA women work collectively in community cooperatives to support their members who are experiencing economic difficulties. This community economic empowerment is supported by various capacity-building programs for strengthening skills and business diversification. As a result, PEKKA women have been able to overcome adversity and emerge stronger after the pandemic. This experience demonstrates that individual women's empowerment and collective empowerment are closely interconnected. The relationship between the two suggests that individual agency can lead to collective empowerment, while, conversely, collective empowerment can also influence individual growth. Through the analysis of gender and class intersectionality, the similarity of the background of women who are members of the PEKKA cooperative strengthens the bonds between them and becomes a significant driver to overcome adversity. In contrast, cooperatives with heterogeneous members tend to experience decline.